Tools and Teaching Strategies for Vocabulary Assessment and Instruction: A Review - E. Dujardin; P. Auphan; N. Bailloud; J. Ecalle; A. Magnan (Social Education Research, 2021)
Vocabulary is a complex intermediate component between oral and written language, whose influence on associated skills and general language abilities (e.g., decoding processes, comprehension) has been largely studied in children, suggesting its important role in literacy. The main aim of this article is to review some questions on vocabulary assessment and stimulation in children and to identify the advantages of new technologies for evaluating and training vocabulary. It seems necessary to emphasize the importance of vocabulary in language and literacy development, as well as the heterogeneity of vocabulary acquisition, depending on preschool word exposure (e.g., familial environment). After a state-of-the-art review of the conceptualization of vocabulary, we revisit assumptions on vocabulary assessment and instruction, indicating the main existing tools. This review aims to enhance perspectives for new valid and effective tools using digital technologies.